Tertiary students' perspective on factors that cause academic plagiarism - Lotfie, Maskanah Mohammad (2013)
That academic plagiarism is on the rise is an alarming world-wide phenomenon. Plagiarism could be present in undergraduate students’ academic writing in the form of extended pieces of perfect but blatantly copied work. It could also be found in deceptively inconspicuous smaller portions of unattributed prose. Factors causing students plagiarising behaviour need to be identified and understood prior to designing and applying measures to curb the problem.